Bleach method in comparison with NALC-NaOH specimen processing method for the detection of mycobacterium in sputum specimen - G., Amar Kumar; Chandrasekaran, S.; J., Visalasree; B., Vignesh Kanna (International Journal of Research in Medical Sciences, 2017)
Background: Tuberculosis is an infectious disease still remains to be a foremost public health risk worldwide. Even though there is an availability of many highly sensitive diagnostic tools, early case detection plays a significant role in control of the disease which relies specially on the detection of acid-fast bacilli in clinical samples which is low sensitive. Earlier decontamination of sputum sample may improve the detection of mycobacterium. Methods: A prospective study was conducted with a total of (N=464) clinically suspected TB patient sputum samples which were collected and processed directly for AFB. From which AFB +ve samples were excluded. The direct AFB -ve (N=279) samples were processed using concentration methods (NALC, Bleach). After concentration, smears were examined under oil immersion for acid fast bacilli by ZN staining. Results: Out of 464 sputum samples, 185 direct ZN stain +ve were excluded. Among the ZN-ve (N=279) samples, n=44 (15.7%) were positive using bleach method. The positivity has improved to n=48 (17.2%) using NALC-NaOH. Conclusions: Bleach method of sputum decontamination is comparable to standard NALC-NaOH method. Therefore, we conclude that the identification of AFB using bleach concentration method can be used in resource limited health care setups especially in laboratories where mycobacterial culture is not performed which might help us in early diagnosis of tuberculosis.